Pelatihan Bantuan Hidup Dasar bagi Orang Awam di Kelurahan Jatibaru Kota Bima - Julhana; Indra Rahmad; Fadlurahmi; Ahmad (Jurnal Pengabdian Masyarakat Cendikia Jenius, 2025)
This community service program was designed to enhance the knowledge and skills of the community, particularly women in Jatibaru Village, Bima City, in early detection of breast cancer through Breast Self-Examination (BSE). The implementation consisted of several stages, including Focus Group Discussions (FGD) with health workers from the Jatibaru Community Health Center, educational sessions on breast cancer and its prevention, and practical training on BSE techniques supported by leaflets and video media. Thirty participants took part in this activity, beginning with a pretest to assess their baseline knowledge, followed by interactive education and hands-on practice, and concluded with a posttest to measure improvements. The findings demonstrated a significant increase in both knowledge and skills. During the pretest, 40% of participants had low knowledge, and 50% had moderate knowledge. After the intervention, posttest results indicated that 73.3% had good knowledge, while 26.7% showed moderate knowledge. In terms of skills, 93.3% of participants were able to perform BSE correctly following the training. These results confirm that education combined with visual media and practical training is highly effective in improving community understanding and skills related to breast cancer early detection through BSE.